Communication between Astronauts and Nasa Deep Space Network: A Conversation Analysis - Aristha , M. Rouzhi; Putri, Dian Marisha; Mono , Umar (Universitas Pendidikan Ganesha, 2023)
In the field of conversation analysis, conversation is one way to approach social order. Conversations are not the seemingly disorganized and random objects they seem at first. This is a special locus of interaction where changes in speakers are repeated (occur), the parties speak at the same time. Gapless and non-overlapping transitions are common. The aim of this study is to analyze aspects of conversation analysis use in communication between Astronauts and NASA Deep Space Network (DSN) under the framework. This study use qualitative descriptive method is applied in this research. The data are collected by transcribe their utterances from Youtube and transcribing their utterances directly into written text. The result of this study shows that 6 types of adjacency pairs, from the data analysis found there are 47 utterances that consist of adjacency pairs. From the findings, there are 7 requesting – agreement, 11 assessment – agreement, 17 question – answer, 1 compliment – acceptance, 1 complaint – apology, 10 offer - acceptance for adjacency pairs.